The Person in the Process of Music Culture Lessons Pedagogical Aspects of Maturity Formation - Rustamjonova Dilkhavas Ravshvnbek qizi (International Journal on Orange Technologies, 2023)
This article talks about how to prepare future music teachers for school education by focusing on extracurricular activities - the work of art clubs, which in this process will create the necessary conditions for their independent and creative work.